Functional equivalence of native light-sensitive channels in the Drosophila trp301 mutant and TRPL cation channels expressed in a stably transfected Drosophila cell line. - Hardie, R.C.; Reuss, H.; Lansdell, S.J.; Millar, N.S. (Cell Calcium, 1997)
Drosophila photoreceptors express two putative cation channels encoded by the transient receptor potential (trp) and trp-like (trpl) genes, which represent prototypical members of a novel family of phosphoinositide-regulated calcium influx channels. Mutations of both trp and trpl selectively abolish components of the light-sensitive current and, when heterologously expressed, both generate cation permeable conductances; however, a detailed comparison of recombinant and native channel properties is lacking. To more rigorously test the hypothesis that TRPL channels mediate one component of the light-sensitive current we have generated cell lines (Drosophila S2 cells) stably transfected with trpl cDNA and compared the recombinant channel properties with those of the light-sensitive conductance in situ in a Drosophila trp mutant under identical conditions. We found close correspondence in respect of a number of quantifiable biophysical parameters including: current voltage relationships, ionic selectivity, voltage independent block by external Mg2+ ions and effective single channel conductance and gating kinetics derived by noise analysis. Our estimate of 60-70 pS for channel conductance was confirmed directly in patch clamp recordings of single TRPL channels in S2 cells. These findings indicate that channels encoded by the trpl gene can completely account for the component of the light-sensitive conductance remaining in the trp mutant.